The Chronology of Settlements with Pre-Inca and Inca Occupations Superimposed: the Case of Pucará de Tilcara (Humahuaca Gorge, Argentina) - Greco Mainero, Mariano Catriel (2016)
The region of the Central and South Andes was, in about the ninth and 15th centuries ad, the stage for the development of political systems tending towards demographic centralization in villages with defensive structures, known as Pucará. The chronological accuracy for these phenomena still remains uncertain, mainly because it involves intervals of long and superimposed occupations, masked by the Inca domination. Thus, this paper analyses the history of the occupation at Pucará de Tilcara, one of the biggest populated centres of the Humahuaca Gorge (Quebrada de Humahuaca, Argentina). Twenty-five radiocarbon dates are critically evaluated to judge its reliability. The Bayesian statistics show that all the dated spaces were used on a long-term basis. The most ancient signs are in the middens and relate at least to the 10th century ad, and the occupation of the housing areas could be calculated to the 13th and 16th centuries. A phase of higher intensity of occupation is observed during the Inca period. This redefinition of this site occupation shows the need to statistically analyse the dates in order to differentiate the phases of occupation.